CONDITIONS OF TECHNICAL CREATIVITY AT VARIOUS STAGES OF EDUCATION - Noga, Henryk; Garbarz-Glos, Barbara; Pytel, Krzysztof; Migo, Piotr (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Creativity develops, regardless of the age we are, it is never too late to find owns passion for creativity , which in my opinion is hidden somewhere in the depths of ourselves. Creativity involves the area of passion, with interesting way of spending time with the creating of unique objects, proper motivation and the desire to obtain gratifications and possibility to show created works. The study shows selected conditions of students technical creativity at different stages of education. The aim of the study was It was to analyse the determinants of creativity in the various stages of education in Poland. Research took place in junior high school. On the basis of research factors that create creativity are: knowledge, abilities and skills, the ability to develop their own individual interests, level of motivation.